Assessment awareness of issues related to e-waste A field study on a sample of Tishreen University students - شريبه, بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aims to reveal the awareness of Tishreen University's students of some issues related to electronic waste. To achieve this goal, a two-part questionnaire was created. The first part covers three dimensions of general awareness of e-waste (knowledge, attitudes, and behavior). The second part includes closed questions with a view to collecting data on certain e-waste issues. The researcher used a descriptive analysis method. The research was conducted on a sample of (194) students, selected by a simple random method. As a result, it was found that the level of e-waste awareness among students at Tishreen University was low, and females were more knowledgeable about e-waste-related issues than males. In light of these findings, the researcher advocated for increasing environmental awareness in general, and awareness of electronic waste in particular, in order to reduce the harmful effects of electronic waste.